2017
DOI: 10.26532/sainsmed.v8i1.1006
|View full text |Cite
|
Sign up to set email alerts
|

Nigella Sativa Seed Extract Ointment Increasing the Amount of Healing Fibroblast and Collagen on Balb/C Mice

Abstract: LATAR BELAKANG: Luka tidak sembuh dalam waktu lama dengan berbagai penyebab merupakan masalah yang sering ditemukan dalam berbagai disiplin kedokteran. Kejadian ini salah satu sumber utama morbiditas, penyebab gangguan psikologis para penderita, meningkatkan biaya pengobatan dan kehilangan jam kerja pada penderita usia produktif.�TUJUAN: untuk mengetahui pengaruh ekstrak biji jinten hitam (Nigella sativa) dalam sediaan salep sebanyak 40% dan 60% terhadap jumlah fibroblas dan kolagen pada penyembuhan lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…From the analysis using the Mann Whitney statistical, they did confirm that the NS-40 had a significantly higher number of fibroblast than the negative controlled group (CN) together with the NS-60. As for collagen present at the wound site, it was found that NS-60 had the highest amount while the lowest was found in the CN (Mastuti et al, 2017).…”
Section: Microscopic Analysismentioning
confidence: 98%
“…From the analysis using the Mann Whitney statistical, they did confirm that the NS-40 had a significantly higher number of fibroblast than the negative controlled group (CN) together with the NS-60. As for collagen present at the wound site, it was found that NS-60 had the highest amount while the lowest was found in the CN (Mastuti et al, 2017).…”
Section: Microscopic Analysismentioning
confidence: 98%